Relationship Between Host Factors and the Incidence of Pulmonary Tuberculosis in HIV/AIDS Patients at Dr. Pirngadi Medan General Hospital - Ali Napiah Nasution; Novianti Nasution; Yolanda Eliza Putra Lubis (Universitas Islam Negeri Sumatera Utara, Medan, 2026)
Tuberculosis (TB) remains a major cause of morbidity and mortality among people living with HIV/AIDS. While CD4 count is a standard clinical indicator, inexpensive hematological indices such as the neutrophil-to-lymphocyte ratio (NLR), monocyte-to-lymphocyte ratio (MLR), and systemic immune-inflammation index (SII) have been proposed as practical markers of immune status. This study examined the association between host factors (sociodemographics, CD4 count, and clinical stage) and hematological indices (NLR, MLR, and SII) with pulmonary TB among HIV/AIDS patients at Dr. Pirngadi Medan General Hospital. An analytical cross-sectional design with a retrospective approach was applied using secondary data from medical records of patients registered between 2022 and 2024. A total of 94 eligible patients were included through total sampling, and data were analyzed using the Chi-square test (p < 0.05). The pulmonary TB was identified in 43.6% of patients. CD4 count showed a significant association with TB occurrence (p = 0.03), with cases more frequent among patients with CD4 <200 cells/mm³. No significant associations were observed for age, sex, employment, marital status, clinical stage, or hematological indices (NLR, MLR, and SII) (p > 0.05). Thus, CD4 count remains the key predictor of pulmonary TB risk, underscoring the importance of intensified TB screening in individuals with advanced immunosuppression. Larger studies are warranted to clarify the potential role of hematological indices in TB-HIV coinfection. Keywords: HIV/AIDS, Pulmonary Tuberculosis, CD4 Count, NLR, MLR, SII.